PEMBELAJARAN STEAM MELALUI MEDIA CERITA ANIMASI UNTUK KELOMPOK B DI RA ABDULLAH BIN UMAR GEDANGAN-MALANG - Rohmawati , Afifatu; Prisdiana , Emilia (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2022)
STEAM is a learning approach that combines six disciplines including Science, Technology, Engineering, Art, and Mathematics through storytelling techniques. Stories as a method that stimulates the development of children's language skills. research objectives of STEAM learning in animated story media for children in group B. The research method used is qualitative with descriptive research type. Collecting data through observation, interviews, and documentation. Data analysis includes data reduction, data display, and conclusion drawing. The results of research and discussion that are able to develop critical thinking skills based on children's experiences optimally. The material is packaged in a simple manner on speaking techniques and listening to a story with the theme of four-legged animals. In addition, it aims to get children's creativity related to adding vocabulary through storytelling methods that can increase self-confidence. Suggestions for teacher research can stimulate children's brain development through interactive learning media with a combination of implementing conceptual learning methods.